An Integrated Landscape Approach for Socially Inclusive Peatland Restoration - Timothy Jessup; Hendrik Segah; Marcel Silvius; Grahame Applegate; Yasurum Jagau (Journal of Wetlands Environmental Management, 2020)
Successful restoration and fire prevention in peat landscapes require full rewetting and permanent revegetation for optimal water retention. The ecological and socio-economic heterogeneity of these landscapes calls for integrated approaches based on participatory zonation and locally appropriate business models. Primary activities in deep-peat core zones are blocking of drainage canals and revegetation; in shallow-peat buffer zones, forestry and agroforestry on fully rewetted peat, aquaculture, and duck farming; while on surrounding non-peat mineral soils, more intensive tree plantations and agriculture. Community-oriented enterprises require private investment, including microfinance. Blended public and private investment is needed for core-zone restoration. Assuming restoration costs of USD 250-1,000 per ha on moderately drained peat, with emissions of 40tCO2/ha/year, carbon finance could pay for the cost of restoration in under 10 years if emissions are fully or largely abated. To stimulate investment in multiple peatland landscapes we propose a provincial ‘enabling platform’ to support participatory zoning, project design, and monitoring based on common standards and methodologies; technical assistance and incubation for project start-up; multi-stakeholder support for enabling policies, plans and institutions; strengthened finance mechanisms and bundled investments for large and small enterprises; and robust scientific support and knowledge exchange.